ANALISIS KELAYAKAN USAHA INDUSTRI RUMAH TANGGA SARUNG TENUN ALAT TRADISIONAL DESA GEDANGKULUT GRESIK - Fatikah Nur Alfizah; Wahyu Hidayat Riyanto; Novi Primita Sari (Program Studi Ekonomi Pembangunan, 2020)
The development of UMKM for traditional tool woven sarongs in Gresik Regency is the most important part in driving economic development, but in the development process, especially in Gedangkulut Village, the traditional tool sarong weaving business does not have the ability to develop forward in terms of marketing and in managing financial management. The purpose of this study was to study the feasibility of a traditional home industry industry of woven gloves in the traditional village of Gedangkulut Village, Cerme District, Gresik Regency, by searching for business or project information. The method used in this research is quantitative and qualitative descriptive. The sample used was 15 respondents. The study uses primary and secondary data. The analytical tool used is to calculate the micro with the formula π = TR - TC, benefit cost ratio, salary period, net present value and return on investment. The results showed the characteristics of the business did not involve the administration of personal finance still united with the financial business, entrepreneurs who did not have a business permit, did not need a business organizational structure and the results of the business feasibility calculations resulted in an average amount of Rp. 483,371,863 for 5 years using the b / c ratio of Rp. 10.8 which means the business is feasible to be carried out, the paybeck period is obtained an average time of less than one year which means good business, net present value is obtained with a positive number of Rp. 7,095,083,053.67 which means the investment is received and the return on investment is obtained by an average of 10.2% which means the ratio is smaller or less good.